Oxymatrine promotes hypertrophic scar repair through reduced human scar fibroblast viability, collagen and induced apoptosis via autophagy inhibition. Issue 5 (8th November 2021) - Deng, Xingwang; Zhao, Fang; Zhao, Dan; Zhang, Qing; Zhu, Yongzhao; Chen, Qian; Qiang, Lijuan; Xie, Nan; Ma, Jiaxiang; Pan, Xiaoliang; Wu, Yinsheng; Guan, Lifeng; et al.
Abstract: Scars are common complications of burns and trauma, resulting in mental trauma, physical pain, and a heavy financial burden for patients. Specific and effective anti‐scarring drugs are lacking in clinical practice. Phytochemicals are easily accessible, low in toxicity, and have various biological and pharmacological properties. Oxymatrine is a phytochemical that regulates autophagy networks. Autophagy is closely related to the maintenance, activity, differentiation, and life‐death of skin fibroblasts during wound repair, which results in pathological scars. We hypothesised that oxymatrine may promote hypertrophic scar repair by inhibiting fibroblast autophagy. In vitro studies showed that inhibition of autophagy by oxymatrine decreased viability and collagen metabolism, and increased apoptosis of human scar fibroblasts (HSFs). In vivo studies showed that inhibition of autophagy by oxymatrine promoted scar repair, resulting in a significantly improved final outcome of the hypertrophic scars, a smaller scar area, decreased epidermal and dermal thickness, and a significant downregulation of CK10, P63, collagen I, α‐SMA, and TGF‐β1. In summary, oxymatrine promoted hypertrophic scar repair by decreasing HSF viability and collagen, and inducing apoptosis via autophagy inhibition. This study provides a new perspective on the mechanism of hypertrophic burn scar formation, as well as key scientific data for the application of the phytochemical oxymatrine as a new method for the prevention and treatment of hypertrophic scars.